[COMMEND YOU AND TOBACCO INSTITUTE FOR OUTSTANDING JOB DONE IN PRODUCING THE FIRECARE VHS VIDEOCASSETTE TITLED A COMMITMENT FOR LIFE FOR SENIOR CITIZENS] (Tufts Archival Research Center, 2007)
Letter from Robert J. Ward, fire chief of the West Hazleton, PA fire department to Karen Fernicola of the Tobacco Institute, thanking her for the informational video he received "A Commitment for Life for Senior Citizens". Says that the video presentation has been exceedingly helpful.